Budaya Politik Lokal Dalam Pelaksanaan Pemilu Di Nagori Urung Panei Kecamatan Purba Kabupaten Simalungun - Tri Mei Rosalya Purba; Julia Ivanna (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
General elections are a means for the people to show that they have sovereignty. This concept implies that the people are the highest power holders in the country and they themselves determine the form and way the government is run. The implementation of regional head elections also reflects this understanding. In general, general elections aim to ensure that the transfer of government power occurs peacefully, regularly, and in accordance with the mechanisms guaranteed and regulated by the constitution. Political culture is a system of values ​​and beliefs held by a society. However, each element of society has a different political culture, for example between society and its elites. It is necessary to develop a political-cultural character where "political" activities are no longer the arena of the ruling elite, but as a means of fulfilling the basic needs of the people in producing mutual benefits (public goods). The method used is library research, collecting data by searching for sources and constructing them from various sources such as books, journals and existing research. The result is that qualitative research is carried out with a research design where the findings are not obtained through statistical procedures or in the form of calculations, but rather aims to reveal phenomena holistically-contextually by collecting data from natural settings and using researchers as key instruments. To understand political culture, you must first understand the meaning of culture and politics.